Biaya Outsorcing Vs Produksi Internal Bahan Baku Utama untuk Pembuatan Mie: Kerangka Pengambilan Keputusan - Winda Hutabarat; Anna Maria Simbolon; Lusiana F Rajagukguk; Rista Marsaulina Sianturi; Hamonangan Siallagan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The noodle manufacturing industry has to make an important decision about sourcing its main raw material: whether to produce it in-house or outsource it. This decision is very important because it affects the quality of the final product and production costs. Production volume, material quality and supply chain reliability are some of the factors that influence the choice between in-house production and outsourcing, according to a review of relevant literature and industry data. In-house production can ensure quality control and supply chain reliability, but may require large investments in infrastructure and labor. Outsourcing, on the other hand, can reduce costs by taking advantage of external suppliers' economies of scale, but it also risks sacrificing quality control and reliability. The aim of this research is to provide noodle manufacturers with a decision-making framework that can be used to evaluate the benefits and costs of outsourcing and in-house production. A hybrid approach combining in-house production and outsourcing is suggested as a solution to optimize quality control and save costs. This study helps noodle manufacturers make strategic decisions about raw material procurement, increasing their competitiveness in the market.